Penerapan Teknik Self Management melalui Bimbingan Kelompok untuk Meningkatkan Tanggung Jawab Belajar Siswa SMP NU Lemahabang - Murthosiyah, Dewi; Novianti, Herny; Kurnia, Rina (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2025)
Learning responsibility should be embedded in each student. In reality, there are still many students who have low learning responsibility. Like the students of class VIII of SMP NU Lemahabang, namely lazy students in the learning process, often delay doing assignments, skip school, and are late to school, which reflects low learning responsibility. This study aims to determine the description of the learning responsibility of SMP NU Lemahabang students, analyze the application of self-management techniques through group guidance to improve the learning responsibility of SMP NU Lemahabang students, determine the description of self-management of SMP NU Lemahabang students after the application of self-management techniques, and identify obstacles that occur in the application of self-management techniques through group guidance to improve the learning responsibility of SMP NU Lemahabang students. This study is a qualitative study. The research informants were the BK teacher and 5 students. Data collection was carried out through observation, interviews, and documentation. The results of this study are self-management techniques consisting of 4 steps, including (a) Self Monitoring (b). Stimulus-Control (c). Self Reward d). Self as Model is able to increase the learning responsibility of SMP NU Lemahabang students, both in terms of perseverance, independence, and positive attitudes.